DEVELOPMENT OF THE REHABILITATION SYSTEM IN UKRAINE. ORGANIZATIONAL ASPECTS - Sitenko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The war and Russian aggression against Ukraine require government and society long-term extraordinary efforts. It’s not only in the field of the destroyed economy. The primary necessity is to restore a dignified life to every person affected by the war, military or civilian. The fate of each of us, our society, and our country in general will depend on efforts effectiveness in this direction. Objective. To develop and substantiate proposals for a systematic approach to the provision of medical rehabilitation assistance in the country. Results. The principles on which it is expedient to create a system of rehabilitation assistance in Ukraine have been formulated and substantiated. They are the principles of statehood, modernity, science, continuity, phasing and unified tactics, regionalism, specializations, self-rehabilitation. Each principle is briefly described, the experience of the world’s leading countries is given. The state and society role in the rehabilitation process is noted. Proposals. Develop a strategy, concept and government program for creating a rehabilitation assistance system in Ukraine. Provide a construction and equipment of regional rehabilitation centers (RC) within the post-war country renovation program. It has to be used worldwide principles of new hospital’s design and construction regarding the 200 inpatient beds in the unit. To locate RC outside of big cities, usually. Training of rehabilitation specialists should be provided in various levels medical educational institutions. Modified vehicles to manual control for disable people and training in its use. To prevent the liquidation of Ukrainian Research Prosthetics Institution. To transfer this institution functions and the property complex to Sytenko Institute of Spine and Joint Pathology National Ukrainian Academy of Medical Sciences. To transfer research medical rehabilitation organizer and executor functions to the National Ukrainian Academy of Medical Sciences, in generally.